A qualitative study on the perspectives of HIV activists on HIV disclosure in Turkey - Yediveren, Oğulcan. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
The literature suggests that public health measures, which are vital to preventing the HIV epidemic, and the right to privacy of people living with HIV often come into conflict. Public health measures follow a strategy to combat the epidemic that focuses on identifying the HIV status of people living with HIV and taking measures to stop transmission. However, this strategy raises privacy and confidentiality concerns for people living with HIV. The thesis seeks to understand how HIV activists manage the tension between public health measures and the rights of people living with HIV as they develop their perspectives on sharing HIV status. Within the scope of the research, one-on-one structured in-depth interviews were conducted with eight HIV activists. The findings of this thesis are based on a thematic analysis of the interviews. The findings of the thesis are presented under three headings: Experiences of people living with HIV while disclosing their HIV status, HIV activists' perspectives on disclosing their HIV status, and factors affecting the decisions of people living with HIV to disclose their HIV status. The main finding of the thesis is that the HIV activists interviewed embrace the idea that HIV disclosure is not an obligation. In justifying this idea, the participants pointed to the discrimination they were exposed to after disclosing their HIV status, the fatigue of disclosing their HIV status to everyone and informing the disclosed people about HIV, the right to privacy and the Undetectable=Untransmittable campaign.
Keywords: HIV (Viruses); HIV infections -- Turkey.